Weighted gene co‐expression network analysis reveals potential candidate genes affecting drip loss in pork. (28th September 2020) - Zhao, X.; Wang, C.; Wang, Y.; Zhou, L.; Hu, H.; Bai, L.; Wang, J.
Summary: Drip loss is an essential evaluation indicator for pork quality. It is closely related to other meat quality indicators, including water‐holding capacity, water loss rate and pH value at 45 min (pH1 ) and 24 h post‐mortem (pH2 ), and is influenced by environmental and genetic factors and their interactions. We previously conducted differentially expressed gene analysis to identify candidate genes affecting drip loss using eight individuals with extremely high‐ and low‐drip loss selected from 28 purebred Duroc pigs. Using 28 identical samples, in the present study, we performed weighted gene co‐expression network analysis with drip loss and drip loss‐related traits, including water‐holding capacity, water loss rate, pH1 and pH2 . A total of 25 modules were identified, and five of them correlated with at least two drip loss or drip loss‐related traits. After functional enrichment analysis of genes in the five modules, three modules were found to be critical, as their genes were significantly involved in amino acid metabolism, immune response and apoptosis, which have potential relationships with drip loss. Furthermore, we identified five candidate genes affecting drip loss in one critical module, AASS, BCKDHB, ALDH6A1, MUT and MCCC1, as they overlapped with differentially expressed genes detected in our previous study, exhibited protein–protein interactions and had potential biological functions in affecting drip loss according to the literature. The outcomes of the present study enhance our understanding of the molecular mechanisms underlying drip loss and will aid in improving the pork quality.